IMPLEMENTASI JOYFUL LEARNING DALAM MENUMBUHKAN KOLABORASI SISWA KELAS IV SEKOLAH DASAR - Iksannudhin, Wijang; Anggraeni Siwi, Dwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation and Joyful Learning approach in fostering collaboration among fourth-grade elementary school students. It employed a qualitative approach with a case study method conducted at SD Negeri Mertan 03 Sukoharjo. Data were collected through observation, interviews, and documentation, and validated using triangulation. Data analysis followed the Miles and Huberman model. The results show that Joyful Learning was implemented through systematic planning, implementation, and evaluation using engaging activities such as group discussions, educational games, and collaborative projects, which improved students’ participation, communication, teamwork, responsibility, and self-confidence. Thus, Joyful Learning is effective in enhancing students’ collaboration skills.